2022
DOI: 10.1002/hpm.3503
|View full text |Cite
|
Sign up to set email alerts
|

Missed initial appointments at Israeli child development centres: Rate, reasons, and associated characteristics

Abstract: Introduction Missed appointments (MAs) at child development centres (ChDCs) cause multiple problems: they preclude timely diagnosis and treatment of both the invited child and children whose appointment was delayed due to overbooking, as well as disrupting efficient organisational management. The aim of this study was to assess the rate and describe the reasons for missed appointments at Israeli ChDCs, and to evaluate the association of socio‐demographic, clinical, and administrative variables with MA rates. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…An Israeli study carried out in Shaare Zedek Medical Center found that 15% of ENT appointments and 16% of orthopedics appointments did not take place due to patient no-show [ 4 ]. Another study, which examined reasons for no-show in child development centers, observed an average rate of 26.6%, with the most common reason being an unexpected event (26.0%), followed by problems in obtaining a financial commitment from the HP that is paying for the treatment (23.4%) [ 5 ].…”
Section: Main Textmentioning
confidence: 99%
“…An Israeli study carried out in Shaare Zedek Medical Center found that 15% of ENT appointments and 16% of orthopedics appointments did not take place due to patient no-show [ 4 ]. Another study, which examined reasons for no-show in child development centers, observed an average rate of 26.6%, with the most common reason being an unexpected event (26.0%), followed by problems in obtaining a financial commitment from the HP that is paying for the treatment (23.4%) [ 5 ].…”
Section: Main Textmentioning
confidence: 99%